IMPLEMENTATION OF SOCIAL MEDIA CONTENT CREATION ON BILAL PRODUCTION'S INSTAGRAM ACCOUNT - Rendi Herdiana Putra; Liestyowati (RADJA PUBLIKA, 2025)
This research aims to implement marketing content creation on the Instagram social media account @Bilal.Id owned by Bilal Production. The background of this study is based on the low level of digital marketing activities conducted by Bilal Production, as well as the lack of consistency in content creation and posting on their Instagram account. This research employs a descriptive qualitative method with data collection techniques including interviews, observation, and documentation. The strategy applied in this study refers to the POAC principles (Planning, Organizing, Actuating, and Controlling) to design, manage, and evaluate effective content management. The results show that systematic planning, structured content scheduling, and the use of diverse content formats significantly improved the performance of Bilal Production's Instagram account. During the implementation period, there was a notable increase in post views, interactions, profile visits, and follower growth, reflecting the effectiveness of the content strategy applied. Instagram insights recorded 683 post views, 452 interactions, and an increase in followers reaching 517 accounts in less than two months. These findings indicate that consistent and well-directed social media content management can serve as an effective strategy for enhancing audience engagement and expanding market reach for SMEs in the digital era.